Vadba z bremeni pri vzdržljivostnih športnikih - Pleša, Jernej (Šport (Ljubljana), 2021)
The most important predictors of performance in endurance sports are maximal oxygen uptake, the second lactate threshold or critical power and movement efficiency. For a long time it was believed that resistance training is not suitable for endurance athletes due to unwanted increases in muscle mass and training of muscle fibres that are not important for those athletes. Based on the literature review that we performed we conclude that resistance training positively affects numerous important determinants of endurance performance and that there are no downsides reported. Studies report that addition of resistance training can have possitive effects as only as 8 weeks after the onset of such training. Resistance training can thus very effectively contribute towards better performance provided that exercise is designed according to the needs of a discipline and the athlete. The main reasons for efficacy of resistance training appears to be improved movement efficiency, maximal locomotion speed, improvements of anaerobic capacity and concomitant delayed onset of fatigue.
Keywords: cycling; endurance; kolesarjenje; performance; resistance training; running; sport; šport; tek; vadba z bremeni; vzdržljivost; zmogljivost